THE INFLUENCES OF HIGH PERFORMANCE WORK SYSTEM ON TRUST IN MANAGEMENT, AND PERSONAL SAFETY ORIENTATION OF SURABAYA FIRE FIGHTERS - arief, Zainal (Archives of Business Research, 2018)
The aims of this study to verify and analyzes on the influences of High Performance Work Systems, Trust in Management and Personal Safety Orientation of Surabaya Fire Fighters. Research population comprise 240 civil servants from firefighting division has characteristic of 3 UPTD’s (Regional Technical Implementer Unit) that are UPTD I (Central Surabaya), UPTD II (North Surabaya), UPTD III (East Surabaya), Sample size which meeting the criteria as 200 civil servants from firefighting division. This study designed in survey research form, because through questionnaire instruments such as statements to be responded as primary data collecting outcome. Data collection result which stated valid and reliable, then processed to make analysis by employed Structural Equation Modeling (SEM). The result of the study showed that High Performance Work System influence insignificant on Personal Safety Orientation, High Performance Work System have significant influence on Trust in Management, Trust in Management have significant Personal Safety Orientation. The aims of this study to verify and analyzes on the influences of High Performance Work Systems, Trust in Management and Personal Safety Orientation of Surabaya Fire Fighters. Research population comprise 240 civil servants from firefighting division has characteristic of 3 UPTD’s (Regional Technical Implementer Unit) that are UPTD I (Central Surabaya), UPTD II (North Surabaya), UPTD III (East Surabaya), Sample size which meeting the criteria as 200 civil servants from firefighting division. This study designed in survey research form, because through questionnaire instruments such as statements to be responded as primary data collecting outcome. Data collection result which stated valid and reliable, then processed to make analysis by employed Structural Equation Modeling (SEM). The result of the study showed that High Performance Work System influence insignificant on Personal Safety Orientation, High Performance Work System have significant influence on Trust in Management, Trust in Management have significant Personal Safety Orientation.